2021
DOI: 10.1007/s11930-021-00309-4
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Sexual Health During the Pandemic of COVID-19: Declines in Sexual Function and Sexual Pleasure

Abstract: Purpose of the Review The World Health Association declared COVID-19 a pandemic more than 1 year ago. We conducted a systematic review of the literature on the topic of women’s sexual health during the pandemic, with a focus on sexual function and sexual pleasure. Our aim is to describe current findings and to discuss implications for women’s sexual health during this period. Recent Findings Thirty-four articles, from 18 countries, were identified. These studies address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 96 publications
1
25
0
Order By: Relevance
“…However, few studies have examined how these changes occur over time as new parents adjust to new parenthood while navigating a global crisis. A systematic review of the literature from 18 countries assessing women’s sexual health during the COVID-19 pandemic showed deteriorations on sexual desire, sexual frequency, sexual satisfaction, and relationship satisfaction [ 21 ]. In first-time mothers and fathers, COVID-19-related concerns and personal psychological difficulties caused by the pandemic were identified as precursors of dyadic and sexual alterations [ 10 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined how these changes occur over time as new parents adjust to new parenthood while navigating a global crisis. A systematic review of the literature from 18 countries assessing women’s sexual health during the COVID-19 pandemic showed deteriorations on sexual desire, sexual frequency, sexual satisfaction, and relationship satisfaction [ 21 ]. In first-time mothers and fathers, COVID-19-related concerns and personal psychological difficulties caused by the pandemic were identified as precursors of dyadic and sexual alterations [ 10 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the world, various studies showed that people reported less sex during the pandemic, a result that was consistent among participants from Australia, Spain, Turkey, the UK, the USA and Taiwan [7,[49][50][51][52][53][54]. Women seemed to be particularly affected by the changes [55][56][57]. On the contrary, solo sexual activity increased, behaviors such as masturbation or using adult online sites becoming more prevalent for both men and women [7,49,50].…”
Section: Sexuality During the Pandemicmentioning
confidence: 84%
“…Some previous studies suggested that changes in sexual behavior (in particular, a decrease in sexual activity, e.g., reduction in frequency and in casual sex) and an increase in sexual dysfunction were dependent on the social restrictions during the COVID-19 pandemic 51,52]. Moreover, two reviews and one meta-analysis found higher rates of sexual dysfunction and reduced sexual activity during COVID-19-related restrictions [53][54][55].…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis indicated that change in sexual functioning was more significant in women than in men [55]. The scoping review also showed that gender inequalities contributed to lower sexual function and satisfaction during the pandemic [54]. However, most previous research referred to sexual behavior rather than sexual satisfaction, which is more related to subjective assessment of sexual life, relatively independent of the current situation.…”
Section: Discussionmentioning
confidence: 99%